Analisis Putusan Hakim dalam Penjatuhan Sanksi Pidana Kasus Korupsi Ditinjau Berdasarkan Perspektif Hukum Progresif (Studi Putusan Nomor 10/PID.SUS-TPK/2021/PT DKI) - Handayani, Tri Astuti; Pramono, Agus (UKInstitute, 2023)
This study aims to examine the basis for judges' considerations in imposing criminal sanctions on Decision Number 10/Pid.Sus-TPK/2021/PT DKI, as well as reviewing the application of criminal sanctions against perpetrators in Decision Number 10/Pis.Sus-TPK/2021/PT DKI reviewed under progressive law. The research was carried out by applying normative legal research methods, using statutory, conceptual and case approaches. From the results of the research, it shows that both the juridical and non-juridical considerations above, the authors consider that the basis for the judge's considerations is not in accordance with the principle of equality before the law and does not consider the status of the defendant as a law enforcer but instead commits a criminal act of corruption. In the concept of progressive law, judges can actually be more flexible in giving decisions, namely by making discoveries or breakthroughs related to what according to him is currently irrelevant. However, the application of the non-criminal sanction against Attorney Pinangki in Decision Number 10/Pis.Sus-TPK/2021/PT DKI if viewed based on progressive law has not been fulfilled. Because the reduction in prison sentences by the Panel of Judges was not matched by an increase in fines, and in considering the imposition of criminal sanctions, the Panel of Judges only seemed to focus on the gender status of the accused.